2023
DOI: 10.1186/s12893-023-02001-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of prognostic nutritional index (PNI)-monocyte-to-lymphocyte ratio (MLR)-platelet (PLT) score on postoperative outcomes in non-metastatic clear cell renal cell carcinoma

Abstract: Background Prognositic nutritional index (PNI), monocyte-to-lymphocyte ratio (MLR) and platelet (PLT) are associated with tumor survival in many human malignancies. Whereas, no study combined PNI-MLR-PLT score and indicated its predictive significance on the prognosis of patients with non-metastatic clear cell renal cell carcinoma (ccRCC). Methods In this study, we retrospectively collected the clinicopathological characteristics and prognostic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The adverse prognosis underscored the importance of individualized treatment; whereas only pathological tumor stage, tumor grade and lymph node metastasis were de nitely identi ed as the risk factors in European Association of Urology (EAU) guidelines [2]. Recently, several combinations of hematological markers re ecting nutritional and/or systemic in ammatory status have been widely studied, including the neutrophil-to-lymphocyte ratio (NLR), and proven to be related to the poor prognosis in various malignancies [5][6][7][8]. Of note, most previous studies have just revealed the potential relationship between the markers mentioned above and survival outcomes; whereas limited data exist with regard to the prognostic value of incorporating these markers into the basal prediction models which precisely acts as a concern of clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse prognosis underscored the importance of individualized treatment; whereas only pathological tumor stage, tumor grade and lymph node metastasis were de nitely identi ed as the risk factors in European Association of Urology (EAU) guidelines [2]. Recently, several combinations of hematological markers re ecting nutritional and/or systemic in ammatory status have been widely studied, including the neutrophil-to-lymphocyte ratio (NLR), and proven to be related to the poor prognosis in various malignancies [5][6][7][8]. Of note, most previous studies have just revealed the potential relationship between the markers mentioned above and survival outcomes; whereas limited data exist with regard to the prognostic value of incorporating these markers into the basal prediction models which precisely acts as a concern of clinical practice.…”
Section: Introductionmentioning
confidence: 99%